Biosafety during a pandemic: shared resource laboratories rise to the challenge. Issue 1 (4th January 2021) - Aspland, Avrill M.; Douagi, Iyadh; Filby, Andrew; Jellison, Evan R.; Martinez, Lola; Shinko, Diana; Smith, Adrian L.; Tang, Vera A.; Thornton, Sherry
Abstract: Biosafety has always been an important aspect of daily work in any research institution, particularly for cytometry Shared Resources Laboratories (SRLs). SRLs are common‐use spaces that facilitate the sharing of knowledge, expertise, and ideas. This sharing inescapably involves contact and interaction of all those within this working environment on a daily basis. The current pandemic caused by SARS‐CoV‐2 has prompted the re‐evaluation of many policies governing the operations of SRLs. Here we identify and review the unique challenges SRLs face in maintaining biosafety standards, highlighting the potential risks associated with not only cytometry instrumentation and samples, but also the people working with them. We propose possible solutions to safety issues raised by the COVID‐19 pandemic and provide tools for facilities to adapt to evolving guidelines and future challenges. Abstract : Use universal precautions for humans, samples, and instruments alike. We all need to work together to have a safe working environment (SRL staff, researchers, health & safety officers, etc) ‐ open and clear communication is best, Communication, consideration, cooperation, & compliance.